Thermodynamics of solutions of hydrocarbons in low molecular weight poly(isobutylene): a gas chromatographic study - Castells, R.C. (1996)
The reduced chemical potentials (x*) of twenty normal and branched alkanes, cyclohexane and three aromatic hydrocarbons at infinite dilution in polyisobutylene (PIB) were measured by gas-liquid chromatography at five temperatures between 35 and 65°C. Reduced partial molar residual enthalpies (k*) were calculated from the temperature dependence of x*; they are positive for PIB+alkane systems, but smaller than those obtained in former chromatographic studies. Although uncertainties on k* are at least one order of magnitude larger than those on x*, binary X12 Flory parameters obtained from k* display a good correlation with the structural parameter 0ɵv defined as the ratio of the number of hydrogen atoms on methyl groups to the total number of hydrogen atoms in the alkane molecule. Very poor or nil correlation exists between X12 values obtained from x* and 0ɵ1. The evidence is by no means conclusive, but in principie the x* results obtained for PIB + alkane systems could be explained in terms offree volume contributions and of the antipathy between methyl groups on the alkanes molecules and the polymer side groups. Positive partial molar residual entropies were detected for the three aromatic hydrocarbons; their partial molar residual enthalpies are however highly positive, resulting in their poor solvent properties towards PIB.